ANALISIS KAPASITAS RUANG PARKIR SEPEDA MOTOR DI MALUKU CITY MALL (MCM) KOTA AMBON - Teguh Aryanto Tamnge; Sammy G Amaheka; Febrino Wangean (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2026)
A solid conveyor is one of the important pieces of equipment used in palm oil processing industries to transport solid materials continuously. This study aims to describe the fabrication process of a solid conveyor at PT SOCFINDO Tanah Gambus and to analyze the application of Shielded Metal Arc Welding (SMAW) in the manufacturing process. The study was conducted through direct observation during an industrial internship program at the workshop division of PT SOCFINDO Tanah Gambus. The fabrication process included material preparation, cutting, flight screw forming, shaft fabrication, welding, assembly, inspection, and finishing. The results showed that the use of SMAW welding with E7016 electrodes produced strong and stable welded joints suitable for industrial conveyor applications. The conveyor design used a Schedule 80 steel pipe shaft, 8 mm steel plate flight screw, and UNP 100 support frame. The manufacturing process required accuracy in dimensional measurements, welding alignment, and assembly to ensure optimal conveyor performance. The implementation of proper fabrication procedures and welding techniques significantly affected the quality and durability of the solid conveyor used in palm oil processing operations. Keywords: Parking, Dynamic Capacity, Static Capacity, Parking Space Unit, Maluku City Mall